Valoração ambiental do parque urbano do Loteamento Cidade Universitária no município de Passo Fundo/RS - Neckel, Alcindo (2010)
Urban parks promote life quality for the population from Passo Fundo city. The park object of this study has been suffering constant degradations and needs financial resources for improvements and maintenance. This research aims to do the environment valuation of the Loteamento Cidade Universitária Park, analyzing the Willingness to pay (WTP) of the urban population from Passo Fundo for the implantation of improvements, its maintenance and preservation. For this, the current situation of the park is characterized; the improvements to be done in the park according the of different professionals view are identified; the characteristics of the population with the WTP are identified; an economic value for the implantation of improvements, maintenance and preservation of the park were obtained. Two scenes for the valuation of the park was considered and 338 questionnaires were made in domiciles distributed in different places of the city. With the research results different situations were obtained, having been able to infer a value to the park of around R$ 2.531.970, 00 million, value which the population this willing to pay in one year added to its house tax